Confederation’s Casualties:: The “Maritimer” as a Problem in 1960s Toronto - Marquis, Greg (Acadiensis, 2010)
Abstract This article, using census data, reports of government departments, and nongovernmental organizations, print media, and popular culture depictions, explores how Atlantic Canadians (often dubbed “Maritimers”) were problematized in the greater Toronto area during the 1960s. Most migrants blended in, but many retained cultural links through various “east coast” taverns and social clubs. Much like the movement of white economic migrants from Appalachia to the American urban Midwest, the migration of Maritimers and Newfoundlanders prompted mixed responses in Toronto, where officials claimed that poor, rural, undereducated, and unskilled migrants were a source of social pathology.